Deformation Patterns and Control of Existing Tunnels Induced by Coastal Foundation Pit Excavation - Tao Liu; Yunlong Liang; Huadong Peng; Liucheng Yu; Tongju Xing; Yuanzhe Zhan; Jianguo Zheng (Journal of Marine Science and Engineering)
The rapid development of coastal cities has intensified land resource constraints and is leading to an increasing number of foundation pit projects near existing operational tunnels. This necessitates careful consideration of coastal excavation impacts on adjacent tunnels. Taking a foundation pit project in Qingdao as a case study, this paper investigates tunnel deformation through statistical analysis, numerical simulation, and field monitoring. By adjusting numerical model parameters, the research examines the influence of horizontal clearance distances, existing structure burial depths, and different retaining structure configurations on tunnel deformation, providing guidance for deformation control. Key findings include the following: (1) Statistical analysis reveals that tunnels in silty clay strata experience more significant excavation-induced deformation compared to those in silt strata, with relative positional relationships between pits and tunnels playing a critical role. (2) Numerical and monitoring results demonstrate that pit excavation induces tunnel displacement towards the excavation zone. Maximum lateral displacement reached 3.57 mm (simulated) and 4.79 mm (measured), while maximum vertical displacement was 3.11 mm (simulated) and 3.85 mm (measured), all within safety thresholds. (3) Sensitivity analysis shows that shallower tunnels exhibit more pronounced deformations. Increasing horizontal separation distance from 10 m to 25 m reduces deformation by one-third. However, adjusting diaphragm wall thickness and retaining structure embedment depth proves limited in deformation control, necessitating reinforcement measures on the tunnel side. These findings provide valuable references for protecting coastal silty clay stratum tunnels.